Auger Highlights - Antonella Castellina (Acta Polytechnica CTU Proceedings)
The Pierre Auger Observatory has been designed to investigate the origin and nature of the ultra high energy cosmic rays using a hybrid detection technique. A review of selected results is presented, with the emphasis given to the measurement of energy spectrum, mass composition and arrival directions.